1995
DOI: 10.1103/physrevb.52.7849
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in resonant-tunneling superlattices

Abstract: Spatio-temporal chaos is predicted to occur in n-doped semiconductor superlattices with sequential resonant tunneling as their main charge transport mechanism. Under dc voltage bias, undamped time-dependent oscillations of the current (due to the motion and recycling of electric field domain walls) have been observed in recent experiments. Chaos is the result of forcing this natural oscillation by means of an appropriate external microwave signal.Comment: 3 pages, LaTex, RevTex, 3 uuencoded figures (1.2M) are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
95
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 18 publications
2
95
1
Order By: Relevance
“…[5][6][7] Due to the presence of the NDV, the vertical transport in the SL's exhibits nonlinear properties, which result in such phenomena as domain formation, 8 multistability, 9 and selfsustained oscillations. 6,7,10 In this nonlinear system, chaos has also been studied theoretically 11 and experimentally. 12,13 Recently, an explosive bifurcation to chaos has been experimentally observed in the power spectra of a driven SL and unambiguously identified using Poincaré maps.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Due to the presence of the NDV, the vertical transport in the SL's exhibits nonlinear properties, which result in such phenomena as domain formation, 8 multistability, 9 and selfsustained oscillations. 6,7,10 In this nonlinear system, chaos has also been studied theoretically 11 and experimentally. 12,13 Recently, an explosive bifurcation to chaos has been experimentally observed in the power spectra of a driven SL and unambiguously identified using Poincaré maps.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to the latter case, the domain walls move across a larger number of units in the superlattice the lower the dimensionality, due to the different spatial distribution of the electric-field across the array in the three cases. Chaotic transport in GaAs/AlAs superlattices has been theoretically predicted 1 and experimentally demonstrated 2 a few years ago. It was found that, when the main charge transport mechanism is sequential resonant tunneling between adjacent quantum wells, undamped time-dependent oscillations of the current appear.…”
mentioning
confidence: 99%
“…3 Such oscillations are due to the motion and recycling of electric field and charge domain walls in the superlattice. 1 Due to the presence of such natural oscillations, spatiotemporal chaos can be induced by a suitable external oscillating field. 1,4 In recent years, new type of nanostructures, like, e.g., nanotubes, molecular or atomic wires ͑often globally referred to as quantum wires͒, have received considerable attention in view of their possible use as components in future electronic applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…by the application of a bias voltage or by the variation of the doping densities in the wells or in the contacts. The strong non linear transport that results from the Coulomb interaction in these systems presents a rich variety of new physical phenomena: multistability and electric field domains formation [1-3], self sustained oscillations [4], bifurcation to chaos [5], etc. In particular, the current flowing through a weakly coupled doped semiconductor superlattice presents a complicated sawtooth structure with unstable regions of negative differential conductance and multistable regions.…”
mentioning
confidence: 99%